Bioinformatic Characterization of Whole Blood Neutrophils in Pelvic Inflammatory Disease: A Potential Prognostic Indicator for Transumbilical Single-Port Laparoscopic Pelvic Abscess Surgery. (1st April 2022) - Li, Haining; Hu, Yanling; Liu, Dan; Wang, Juanjuan; Han, Panpan; Zhang, Nan; Li, Yan
Abstract : The purpose of this research is to determine the prognosis of patients treated with transumbilical single-port laparoscopic surgery for acute pelvic inflammatory illness. Postoperative data on 129 patients treated with laparoscopic surgery for acute pelvic inflammatory illness were obtained retrospectively. It was observed that the shorter the time required for postoperative leukocyte recovery to normal, the shorter the time required for postoperative pain and diet recovery, as well as hospital stay, in such individuals. CIBERSORT was used to examine patient data from GEO. The most significant difference between the normal and pelvic inflammatory groups was in neutrophil content. Association study found a substantial positive correlation between the quantity of neutrophils infiltrating the immune system and the abundance of monocyte M0 infiltrating the immune system. Neutrophil immune infiltration was strongly inversely linked with plasma cells, activated CD8+ Tm cells, and active CD4+ Tm cells. Four mRNAs linked with pelvic inflammatory illness were revealed to be strongly associated with neutrophil immune infiltration, notably CALML4, COQ10B, DCPS, and PPP2R1A . The ROC revealed that CALML4 (area under the curve (AUC): 0.769, 95% confidence interval (CI): 0.638–0.881), COQ10B (AUC: 0.742, 95% CI: 0.587–0.881), PPP2R1A (AUC: 0.733 95% CI: 0.593–0.857), and DCPS (AUC: 0.745, 95% CI: 0.571–0.900) were potential markers for predicting pelvic inflammatory disease. CALML4, COQ10B, PPP2R1A, and DCPS may be critical determinants determining the amount of preoperative neutrophil infiltration and the time required for leukocyte recovery after single-port laparoscopy in acute pelvic inflammatory illness.